Assessment in online and blended learning environments - Koç, Selma; Liu, Xiongyi; Wachira, Patrick (Emerald Publishing Limited : Information Age Publishing, 2015)
Online and blended learning requires the reconstruction of instructor and learner roles, relations, and practices in many aspects. Assessment becomes an important issue in non-traditional learning environments. Assessment literacy, i.e., understanding assessment and assessment strategies, is critical for both instructors and students in creating online and blended environments that are effective for teaching and learning. Instructors need to identify and implement assessment strategies and methods appropriate to online or blended learning. This includes an understanding of the potential of a variety of technology tools for monitoring student learning and improving their teaching effectiveness. From the students' perspective, good assessment practices can show them what is important to learn and how they should approach learning; hence, engaging them in goal-oriented and self-regulatory cognitions and behaviors. The book targets instructors, instructional designers, and educational leaders who are interested in understanding and implementing either summative or formative assessment in online and blended learning environments. This book will assist the relevant audience in the theory and practice of assessment in online and blended learning environments. Providing both a research and practice perspective, this book can help instructors make the connection between pedagogy and technology tools to maximize their teaching and student learning. Among the questions addressed in this book are: * What assessment strategies can be used in online or blended learning? * How can instructors design effective assessment strategies? * What methods or technology tools can be used for assessment in online or blended learning? * How does peer-assessment work in online or blended learning environments?